Analysis of the risk of ovarian torsion in 49 consecutive pediatric patients treated at a single institution. Issue 2 (4th June 2019) - Sugita, Koshiro; Kawano, Takafumi; Motoi, Mukai; Muraji, Toshihiro; Onishi, Shun; Moriguchi, Tomoe; Yamada, Koji; Yamada, Waka; Masuya, Ryuta; Machigashira, Seiro; Nakame, Kazuhiko; Kaji, Tatsuru; et al.
Abstract : Purpose: An early diagnosis of ovarian torsion is sometimes difficult due to variable clinical symptoms and non-specific imaging findings. We retrospectively reviewed patients with pediatric ovarian masses manifesting torsion. Methods: Fifty-eight ovarian masses (55 episodes) in 49 non-neonatal patients treated from April 1984 to March 2017 were retrospectively analyzed. The Mann-Whitney U test and Fisher's exact test were used for the statistical analysis. Results: The median age of these 55 episodes was 10.5 years old (range 1.0–23.0). Thirty-three patients presented with abdominal pain. Forty-five tumors and 13 cystic masses were resected and diagnosed pathologically (50 benign and 8 malignant). Torsion was identified in 15 cases (25.9%) at operation. The torsion masses were all benign, and 8 ovaries (53.3%) were successfully preserved. Comparing the torsion cases with the non-torsion cases, only the white cell count was significantly higher in the torsion cases (p=0.0133) and in the patients presented with abdominal pain (p=0.0068). The duration of abdominal pain was significantly shorter in ovary preserved cases than in oophorectomy cases. Conclusion: The white blood cell may be a helpful indicator of the presence of torsion as well as the need for surgery.